Neurasthenia and the Rise of Psy Disciplines in Republican China. Issue 2 (1st June 2016) - Wang, Wen-Ji
Abstract : The high prevalence of neurasthenia and its divergent social and cultural meanings in the late nineteenth and early twentieth centuries has been subjected to historical and anthropological studies. The present study explores the history of this elastic diagnosis in relation to the rise of "psy disciplines" in Republican China. Since the 1920s, emergent Chinese neuropsychiatric and mental health professionals eagerly entered the already vibrant culture of neurasthenia and provided their explanations. As China was under different spheres of influence, diverse systems of psy knowledge were practiced in the country. Differences in the conception of the nature of the disease were further intertwined with various reform projects with which these bodies of psychological knowledge were associated. Despite being the products of scientific internationalism, these discourses not only resonated with the epistemological and social concerns derived from Japan, Europe, and, gradually, the United States but generated their own ideas of personal, social, and national regeneration. By examining the history of neurasthenia in the light of the interactions among popular culture, the advent of modern psychiatric and psychological knowledge, and Republican China's striving for modernity amid social turmoil, the article contributes to our understanding of medical culture in modern China.